Pengaruh Kualitas Informasi Akuntansi dan Kapasitas Manajer terhadap Kualitas Keputusan dalam Hubungannya dengan Kinerja Keuangan (Studi pada Badan Layanan Umum Universitas Brawijaya) - Hadiyana, Amalia; hakim, Abdul; Suryadi, Suryadi (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
This research is a descriptive-verificative study, which aims to identify the relationship between management accounting information quality and manager's capacity to decisions quality related to financial performance, studies at the Public Service Board of Brawijaya University. The research was conducted through questionnaire data collection from 63 respondents consisting of leaders in faculties and postgraduate programs, and financial ratios to measure the financial performanceof year 2018. The method of data analysis used was Partial Least Square (PLS). The results of this study indicate that: (a) management accounting information quality has a significant effect on decisions quality; (b) manager capacity has a significant effect on decisions quality; (c) directly, management accounting information quality has no significant effect on financial performance; (d) directly, managers capacity has no significant effect on financial performance; and (e) decisions quality has a significant effect on financial performance.